Evolving Role of Special Schools for Children with Visual Impairment in India - Pankaj Kumar, (JOURNAL OF INDIAN EDUCATION, 2018)
Schools are the place where children and adolescents spend a significant time of their young lives. Student well-being is essentially influenced by the school. Special schools are believed to be an institute specifically dedicated to improving the lives of children and adolescents with disabilities; schools for the visually impaired are one of the forms of special schools. In India special schools for the visually impaired have significantly grown in number after independence. The nature of these schools varies as there are several innovative models of special education being practiced across the country. In the context of the recent development like the Right of Persons with Disabilities Act, 2016, and the Right of Children to Free and Compulsory Education Act, 2009, and Amendment 2012, one needs to look at special schools and inclusive schools as a dichotonomous continuum for education of all children with disabilities, exercising their right to appropriate education. Special schools will continue to have a significant role to play for inclusion of children with visual impairment. This paper explores the role and importance of special schools for the children with blindness and low vision in the country in the present context.